LEGAL PROTECTION OF THE CHILDREN INVOLVED NARCOTICS ABUSE CRIMES IN THE JURISDICTION OF SABANG CITY - Zaizil Ihza Mahendra; Mustamam Mustamam; Panca Sarjana Putra (Jurnal Ilmiah METADATA, 2025)
Legal protection for drug users, according to Law No. 35 of 2009 concerning Narcotics, is provided through medical and social rehabilitation for addicts and victims of abuse. Law No. 35 of 2014 concerning Child Protection provides special protection for children as drug users, which also views children as both victims and perpetrators. Therefore, priority is given to supervision, treatment, and rehabilitation, rather than just criminalization. Legal provisions for children in conflict with the law are in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Legal accountability for children who use narcotics uses a juvenile criminal justice system that prioritizes action and rehabilitation, not just criminal penalties, with a maximum penalty of half the adult penalty. Children are considered both perpetrators and victims, so that in addition to criminal sanctions, judges can also impose rehabilitation and guidance measures to restore children and prevent them from abusing drugs again, in accordance with the Narcotics Law and the Child Protection Law. Legal protection for children as perpetrators of narcotics crimes, if the child is a perpetrator of narcotics abuse, prioritizes the granting of rehabilitation rights over prison sentences.